MEDAN MAKNA PERALATAN RUMAH TANGGA TRADISIONAL DALAM BAHASA JAWA DIALEK TEGAL - Shintia Dwi Alika (STKIP Singkawang, 2022)
AbstractThis study aims to describe the meaning components, the meaning types, and the semantic roles of traditional household appliances in Javanese especially in the Tegal dialect. The method in this research is descriptive-qualitative method. The data of this research are words that contain the meaning field of household appliances in Javanese with the Tegal dialect. The data source in this study is The Javanese Language of the Tegal Dialectwhich is spoken by native speakers of the Tegal community. The technique used is interviewing informants who are native speakers of Javanese Tegal dialect. Data collection tools in this study were a list of questions with pictures or photos, recording devices, and paper. The results of the analysis of the existing data concluded that in The Tegal Dialect of the Javanese Language, there were 17 household items made of plait, 8 from wood, 7 from metal, 2 from stone, 2 from knitted yarn, 3 from clay, 1 from bamboo, and 1 from coconut shells. The analysis also revealed 41 lexical meanings, 5 collocative meanings, and 41 semantic roles of those household appliances.